Finding fairness : from pleistocene foragers to contemporary capitalists - Jennings, Justin (University Press of Florida, 2021)
"Providing a sweeping, archaeologically grounded view of human history, Justin Jennings explores the origins, endurance, and elasticity of ideas about fairness and how these ideas have shaped the development of societies at critical moments over the last 20,000 years"--